Discrete model of twisted rings - Gaspar, Zsolt; Nemeth, Robert (Computer Assisted Methods in Engineering and Science, 2004)
A discrete model consisting N straight links and N springs is defined. The originally straight model is bent into a discrete torus, then it is twisted. The C2 symmetric shapes can be determined by four parameters, and there are three constrains. The equilibrium paths are determined by the simplex method (piecewise linear approximation). Global bifurcation diagrams, spatial equilibrium shapes and parasitic solutions are analysed.